Beyond liberty and property : the process of self-recognition in eighteenth-century political thought - Gunn, J. A. W. (John Alexander Wilson), 1937- (McGill-Queen's studies in the history of ideas, 1983)
The themes explored include political liberty, "legal tyranny," defences of influence in government, recognition of the Opposition, and the development of organic categories of political analysis - the latter in a chapter that explodes the association often presumed between organicism and conservative modes of thought. A chapter on the "Fourth Estate" examines the gradual process of legitimation of "interests," culminating in the influence of the press. Central to the account of new political forces and their recognition is the idea of public opinion, which evolved during this period from the notion of public spirit. Chapters on the classical legacy of the century and on the High-Tories examine two backward-looking aspects of the political cultrure. Tracing the persistent influence of High-Toryism, Gunn questions the conventional wisdom about eighteenth-century ideological consensus in general and Whig solidarity in particular. He demonstrates that theories of government from the seventeenth century survived to a degree not previously admitted by modern scholarship.